Verifying user-generated content (UGC) through the Indonesian Broadcasting Commission (KPI): Maintaining nationalism or threatening freedom of expression? (Tamalanrea: Journal of Government and Development (JGD), 2025)
The revision of the Law on User-Generated Content (UGC) has sparked public debate because it is perceived as potentially limiting freedom of expression. This study examines the implications of the policy, particularly the requirement for content verification through the Indonesian Broadcasting Commission (KPI), and its impact on society and the broadcasting ecosystem. Using a qualitative policy analysis approach based on literature review, media reports, and relevant usage data, this study evaluates the relevance and effectiveness of the regulation. The findings indicate that the verification policy may create practical difficulties, especially considering that approximately 34.7–54.8% of media consumption is dominated by UGC platforms such as YouTube and TikTok. Additionally, KPI is traditionally positioned as a supervisory body for broadcasting institutions rather than individual content creators, leading to regulatory ambiguity. These results suggest that the policy requires further review to avoid negative social impacts, including restrictions on public expression. Collaboration between government, media, and society is essential to maintain nationalism while safeguarding freedom of expression, ensuring that regulatory policies support a healthy broadcasting ecosystem without suppressing public participation.
Keywords: User Generated Content; Freedom of expression; Indonesian Broadcasting Commission; Nationalism; Digital regulation